SISTEM PENUNJANG KEPUTUSAN PENENTUAN PROMOSI JABATAN DENGAN METODE PENILAIAN 360 FEEDBACK BERBASIS WEBSITE - Usanto Usanto; Andy Dharmalau; Septina Alfatikha (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
PT. Jasa Berdikari Logistics is a company engaged in transportation and logistics. Established since 2006, the business that is carried out is in the field of transportation services. In determining the promotion of PT. Jasa Berdikari Logistics does not yet have a method to determine what will happen at this time. It has main problems, namely: There is no definite method in determining the promotion of vacant positions, because of the manual process carried out by HRD because in conducting the assessment. The employee appraisal process of PT Jasa Berdikari Logistics for the purpose of current promotions is still done manually and takes a long time in the employee appraisal process. Along with the development of the organization of PT Jasa Berdikari Logistics, the current assessment system is considered less supportive to be applied or used at PT Jasa Berdikari Logistics. So that the proposed system is expected to simplify and speed up the process and obtain information related to employees. The designed information system has 2 processes, namely, the master process and the transaction process